MEMBANGUN CITRA CAFE GRANDE GARDEN DALAM BINGKAI SOSIAL MEDIA INSTAGRAM - Wahyudi, Anyes; Rokhim, Abdul; Insan Romadhan, Mohammad (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
The fast advancement of business in the present period has brought about progressively savage rivalry. It isn't just about how a business gives items and administrations yet additionally about how the items and administrations that have been made can be known, acknowledged, and trusted by buyers. With current mechanical advances, for example, social media, it assumes a significant part in building the picture of a company. In this research, the specialist plans to figure out how to fabricate a picture of Grande Garden Cafe in the Instagram web-based entertainment outline, where this exploration utilizes new media hypothesis. The technique utilized is a contextual investigation with a qualitative approach.